QUANTUM-SIZE EFFECTS IN THIN FILMS AND NANOSTRUCTURES (review) - Фреїк, Дмитро Михайлович; Харун, Лідія Тарасівна; Соколов, Олександр Леонідович; Юрчишин, Ігор Костянтинович; Потяк, Володимир Юрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The review on size effects in materials of reduced dimensionality, including: metals, semimetals and semiconductors, is done.